Isolation and Characterization of Bacterial Strains that are Resistant to Copper, Mercury and Other Antibacterial Agents From Different Soil Environments. - Jakaria, Tuan Haji Rambli (Universiti Malaysia Sarawak, UNIMAS, 2010)
Bacteria were isolated from soil samples taken from different locations in the Kuching industrial area. Copper- and mercury-resistant strains were selected and minimal inhibitory concentrations (MICs) for either heavy metal were determined. Mercury is more toxic than copper in both solid and liquid media. The inhibitory concentrations in solid media were higher than in liquid media. With higher MIC values, the bacterial isolated from the metal factory area were shown to be more resistant to metals compared to those from the other areas. This acts as a bioindicator of higher levels of heavy metal pollution in the metal factory area. The most dominant metal-resistant bacteria were Pseudomonas sp. About 50% of bacterial strains had multiple heavy metal resistance phenotypes (there were two to seven types of heavy metal). The isolates were also found to be resistant to several antibiotics, including ampicillin, kanamycin and tetracycline. The highest percentage of individual resistance detected was CuR, followed by CoR, FeR, MgR, ZnR, HgR, AgR and UVR. DNA analysis of five strains failed to show the presence of plasmids. Hence, there was no clear indication that the multiple resistances were coded by gene carried on plasmids.